Design Of Student Live Worksheet to Support Students' Computational Thinking Skills Through Differentiation Learning - Echa Alda Melinia; Budi Mulyono; Anita Desiani (UNNES JOURNAL, 2025)
Current mathematics learning methods limit students' computational thinking (CT) skills, because teaching focuses on knowledge and lacks abstraction and algorithmic thinking. To improve CT skills, a differentiated learning approach can be applied, using problem-solving strategies such as direct worksheets and technology-based learning. This study designed a Student Live Worksheet (SLW) for arithmetic sequences and series material, which combines Pagaralam contexts to motivate learning. The ADDIE development model was used to create a valid and practical SLW, which was tested on grade X students of one private vocational school (SMK) in Pagaralam. The SLW, which was validated by three experts, received a validity rating of 84.28% after revision and based on the practicality questionnaire, the percentage of practicality was 89,58%. Its practicality was demonstrated by student engagement during the trial. The SLW is independent, adaptive, and user-friendly, with facilities provided according to students' learning interests, and an attractive design. It serves a variety of electronic devices and fosters creativity in learning. This research can serve as a reference for further development in other mathematical topics to support computational thinking skills. The SLW developed is proven to be valid and practical, and effectively supports students’ computational thinking skills. Therefore, it can be used as a useful tool in differentiated mathematics instruction and adapted to various contexts. Abstrak Metode pembelajaran matematika yang ada saat ini membatasi kemampuan berpikir komputasional (CT) siswa, karena pembelajaran berfokus pada pengetahuan dan kurang abstraksi serta berpikir algoritmik. Untuk meningkatkan kemampuan CT, pendekatan pembelajaran terdiferensiasi dapat diterapkan, dengan menggunakan strategi pemecahan masalah seperti lembar kerja langsung dan pembelajaran berbasis teknologi. Penelitian ini merancang Lembar Kerja Siswa (LKS) untuk materi deret dan deret aritmatika, yang menggabungkan konteks Pagaralam untuk memotivasi pembelajaran. Model pengembangan ADDIE digunakan untuk membuat LKS yang valid dan praktis, yang diuji coba pada siswa kelas X di salah satu SMK swasta di Pagaralam. LKS yang telah divalidasi oleh tiga orang pakar ini memperoleh peringkat validitas sebesar 84,28% setelah direvisi dan berdasarkan angket kepraktisan, persentase kepraktisannya sebesar 89,58%. Kepraktisannya ditunjukkan dengan keterlibatan siswa selama uji coba. LKS bersifat mandiri, adaptif, dan mudah digunakan, dengan fasilitas yang disediakan sesuai dengan minat belajar siswa, dan desain yang menarik. Ini berfungsi untuk berbagai perangkat elektronik dan menumbuhkan kreativitas dalam pembelajaran. Penelitian ini dapat menjadi referensi untuk pengembangan lebih lanjut dalam topik matematika lainnya untuk mendukung keterampilan berpikir komputasional.